Comparative Study of the Effect of Dry and Moist Dressing on Burn Wound - Seyedalshohadaee M; F Rafii; Hoseini AF; Karimi H (Iran University of Medical Sciences, 2012)
Background & Aims: Consistent with recent scientific advances in wound treatment , modern dressing, using technology and knowledge were designed and produced . Such a dressing can provide an appropriate environment for moisturizing wound healing by maintaining and controlling moisture along with other conditions. This study aims to compare the effect of dry and moist dressing on burn wound healing.   Material & Methods: It was a quasi experimental research. Sampling was done constantly according to inclusion criteria. The final sample consisted of 60 patients hospitalized in Shahid Motahari burn center with second degree burn and a TBSA less than or equal to 10% on bo th hands or legs. Data collection tools included demographic information form and observation checklist. Part of the burned area was covered with a dry dressing according to hospital routine and the other part covered with the wet dressing of NA ultra. The stage and duration of wound healing was observed and recorded in the third, seventh , thirteenth and twenty-first days . Data was analyzed using descriptive statistics and pair t-test by SPSS-PC (v. 13).   Results : There was a significant difference between the mean scores of the stage (P<0.001) and duration (P=0.004) of burn wound healing. Conclusion: According to the findings , the use of wet dressings in treating burn wounds is advisable .